Comunidades de energia para condomínios: estudo de caso para o Alphaville Ceará - residencial 1 e 2. 2023 - Araújo, Esdras Miranda de (2023)
The establishment of Distributed Generation (GD) in Brazil has contributed positively to investments in electricity generation using renewable energy sources. As a result, a regulation is needed to keep pace with technological and legal trends, aiming at legal certainty and greater flexibilities in electricity distribution and commercial systems intrinsic to the clean energy market. Investments in Photovoltaic (PV) systems lead the option of investing in renewable energies due to the easy adaptation to constructions, low level of maintenance, financing lines and attractive financial returns with the compensation system. Under this perspective, Energy Communities (CE) emerge, formed by the association of citizens, organizations, and companies that decide, together, to build structures to produce and share renewable energy, with advantages for the environment and economic and social benefits. Prosumers organization in CE, inserted in Intelligent Grids (IR) and managed by a Virtual Power Plant (VPP), It is an alternative for integrating solutions in GD. In this context, the present dissertation aims to analyze the case study of a CE for the condominium Alphaville Ceará – Residential 1 and 2, composed of 1,002 residential lots. The study starts from the standardization of a Family Unit (UF) with an average monthly consumption of 1,158 kWh; using PVSYST, a PV plant of 9.31 kWp is dimensioned, with an estimated investment of R$ 40,000.00. The PV plant is composed of 14 PV modules and average monthly electricity generation of 1,198 kWh/month, with a positive balance per UF of 40 kWh/month. With the UF generation data, extrapolation is performed for different levels of CE adherence (25 %, 50 %, 75 % and 100 %) resulting in monthly consumption of 290 MWh, 580 MWh, 870 MWh and 1,160 MWh, respectively, and installed powers of 2,332 kWp, 4,664 kWp, 6,996 kWp and 9,329 kWp, respectively. The results obtained for the 4 levels of CE participation ratify the potential relevance that an CE obtains according to the growth in the number of participants in relation to generation capacity, installed power and energy balance. All analyzes are referenced in Law No. 14,300, which establishes the legal framework for distributed micro and mini-generation. The results obtained from the financial analyzes for all levels of CE membership show a positive NPV, payback of 3.12 years and an IRR of 34 % > adopted TMA of 13.75 %, indicating that the project is more profitable than cost financial market opportunity.